(untitled) (Al-Farooq Journal of Sciences, 2026)
This study investigates the effect of recycled rubber particles on the compressive strength of concrete using different rubber replacement ratios (9%, 12%, and 15%) and different sand sources (Qarnilia, Sidi Al Sayeh, and Zliten) The experimental results show that. The disposal of waste tires has become a serious environmental challenge worldwide due to their non-biodegradable nature and large accumulation rates. One of the most promising sustainable solutions is the reuse of waste tire rubber in concrete production. Effect of Rubber Particles on the Compressive Strength of Reinforced Concrete Beams.